The Regenerative Efficacy of Aqueous And Methanolic Extracts of Watermelon, Citrullus Lanatus Seeds On Physiological Saline And Acetaminophen-Induced Kidney Damage in Female Albino Rats (British Journal of Multidisciplinary and Advanced Studies, 2022)
Kidneys are important organs that are responsible for osmoregulation in animals. In this research work, extracts of watermelon seeds, Citrullus lanatus L were used for the correction of saline and acetaminophen-induced kidney damage in female albino rats. Aqueous and methanolic extracts were made from watermelon seeds and fed together with vital feed to rats. Forty two (42) female swiss albino rats were purchased and divided into 7 groups (A-G). There were seven rats in each group. The rats in Group A were only given vital feed without any extracts (normal). The rats in Groups B, D and E were given 10g/kg body weight of salt solution while the rats in Groups C, F and G were given 3g/kg body weight of paracetamol. The rats in Groups B and C were the experimental controls. The rats in Groups D and E were fed aqueous extract of watermelon seeds at dosages of 200 mg/kg body weight and 400 mg/kg body weight respectively while the rats in Groups F and G were fed methanolic extract of watermelon seeds at dosages of 200 mg/kg body weight and 400 mg/kg body weight respectively. All the rats were given 40% body weight of vital feed twice daily and they all had access to plenty supply of good drinking water. The experiments were monitored for 28 days. At the end of the 28th day, all the rats were sacrificed and their kidneys were removed for histopathological studies. The results of the histopathological analysis of the kidneys revealed that aqueous and methanolic extract of C. lanatus seeds had healing/ regenerative and nephoprotective effects on the damaged done to the kidneys of rats by overdose of salts and paracetamol.
Keywords: Apoptosis; Aqueous Extract; Citrullus Lanatus; Histopathological; Methanolic Extract; Nephroprotective